Traditional crafts from native North America - Temko, Florence (Minneapolis, MN : Lerner Publications, 1997)
Provides instructions for making such traditional North American Indian crafts as dreamcatchers, beadwork, and cornhusk dolls.
Includes bibliographical references (p. 60-61) and index.
Wilson's Children.
Booklist.
L.A. Recommended Foreign Language.
3.5
3-6
Keywords: Indian craft -- Juvenile literature; Indians of North America -- Industries -- Juvenile literature; Indian craft; Handicraft; Handicraft; Native American art -- North America; Indian craft; Indigenous people of North America -- Juvenile fiction; Handicraft -- Indians of North America